Analysis of the Risk Factors Associated With Obstructive Sleep Apnea Syndrome in Chinese Children - Xiao, Ling; Su, Shuping; Liang, Jia; Jiang, Ying; Shu, Yan; Ding, Ling (Frontiers in Pediatrics, 2022)
Objective: The present study was developed to explore risk factors related to the incidence and severity of obstructive sleep apnea syndrome (OSAS) in children. Methods: Clinical data pertaining to children treated in our department for snoring and mouth breathing were retrospectively reviewed. All children completed a questionnaire and underwent physical examination and polysomnography (PSG). Children were separated into OSAS and primary snoring (PS) groups. Factors associated with these two groups were analyzed, with risk factors significantly associated with OSAS then being identified through logistic regression analyses. OSAS was further subdivided into mild, moderate, and severe subgroups, with correlations between risk factors and OSAS severity then being analyzed. Results: In total, 1550 children were included in the present study, of which 852 and 698 were enrolled in the OSAS and PS groups. In univariate analyses, obesity, family passive smoking, a family history of snoring, allergic rhinitis, asthma, adenoid hypertrophy, and tonsil hypertrophy were all related to pediatric OSAS (P<0.05). In a multivariate logistic regression analysis, adenoid hypertrophy (OR:1.835, 95% CI: 1.482-2.271) and tonsil hypertrophy (OR:1.283,95%CI:1.014-1.622) were independently associated with the risk of pediatric OSAS (P<0.05). Stratification analyses revealed that OSAS incidence increased in a stepwise manner with increases in adenoid and tonsil grading (P<0.01). Correlation analyses revealed adenoid hypertrophy and tonsil hypertrophy in the mild, moderate, and severe subgroups to be positively correlated with OSAS severity (r > 0, P< 0.01). Conclusion: Adenoid hypertrophy and tonsil hypertrophy were independently related to the risk of pediatric OSAS, with both OSAS incidence and severity increasing with the size of the adenoids and tonsils.